2009
DOI: 10.1007/s10549-009-0652-2
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 is associated with epigenetic silencing of BRCA1 in sporadic breast cancer

Abstract: BRCA1 is closely related to the pathogenesis of breast cancer, BRCA1 mRNA is reduced in sporadic breast cancer cells despite the lack of mutations. In the present report, we found that overexpression of UHRF1 (ubiquitin-like, containing PHD and RING finger domains 1) was closely related to DNA methylation, deacetylation, and methylation of histones, recruitment of an inhibiting transcriptional complex on the BRCA1 promoter in sporadic breast cancer. Overexpression of UHRF1 induced deacetylation of histones H3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 32 publications
4
76
0
Order By: Relevance
“…This is also supported by findings in breast tumors, where UHRF1 overexpression was correlated with BRCA1 promoter hypermethylation. 33 To provide additional support to our ex vivo observations, we knocked down the expression of UHRF1 in A549 lung adenocarcinoma cell line. Both UHRF1 knockdown derived clones demonstrated reduced methylation of RASSF1, CYGB, and CDH13 promoters, which are hypermethylated in A549.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This is also supported by findings in breast tumors, where UHRF1 overexpression was correlated with BRCA1 promoter hypermethylation. 33 To provide additional support to our ex vivo observations, we knocked down the expression of UHRF1 in A549 lung adenocarcinoma cell line. Both UHRF1 knockdown derived clones demonstrated reduced methylation of RASSF1, CYGB, and CDH13 promoters, which are hypermethylated in A549.…”
Section: Discussionmentioning
confidence: 88%
“…32 Despite the importance of UHRF1 function in DNA methylation, the current data regarding its contribution to the epigenetic silencing of TSGs in primary human tumors are limited to a single report associating UHRF1 overexpression with BRCA1 promoter methylation in sporadic breast cancer. 33 In this study, we examined the mRNA expression profile of UHRF1 as well as DNMT1, DNMT3A, and DNMT3B in NSCLC and examined their relationship to the methylation status of CDKN2A and RASSF1 gene promoters. In addition, we further investigated the role of UHRF1 in regional hypermethylation by knocking its expression down in a lung cancer cell line.…”
mentioning
confidence: 99%
“…Using a well-established ACI rat model, Kristy R et al identified morphological and epigenetic changes in the mammary gland tissue after exposure to constitutively elevated estrogen levels, and found that progressive hyperproliferative changes were paralleled by epigenetic disturbances, which demonstrates that the hyperacetylation of histone induced by estrogen has a significant role in the early stage of breast cancer development (Kutanzi et al, 2010). Chen et al have reported that p300/CBP and PCAF mediate hyperacetylation of histone H3, H4 and transcriptional activation of ER target genes induced by estrogen in MCF-7 cells (Chen et al, 1999;Jin et al, 2010;Jin et al, 2011). PCAF predominantly acetylates histone H3.…”
Section: Discussionmentioning
confidence: 99%
“…5F; r 2 ¼ 0.63 and P < 0.0001). Because it has been shown that the DNA methyltransferase-1 (DNMT1) binds to BRCA1 promoter inducing its methylation (30) and large-scale 2-hybrid assay revealed that TNRC9 interacted with DNMT1 in mice (31), we examined the role of TNRC9 in DNMT1 activity. The gene silencing of TNRC9 in ZR-75-1 breast cancer cells decreased significantly DNMT1 binding to BRCA1 promoter (Fig.…”
Section: Tnrc9 Induces Brca1 Promoter Methylationmentioning
confidence: 99%